A longitudinal study of self-reported spasticity among individuals with chronic spinal cord injury. Issue 3 (March 2018) - DiPiro, Nicole; Li, Chao; Krause, James
Abstract Study design A longitudinal study. Objectives To describe the prevalence and stability of self-reported spasticity severity in adults with chronic spinal cord injury (SCI) over a 3-year timeframe and examine predictors of severity and change in spasticity severity. Setting The data were collected by mail at a medical university in the Southeastern United States. Methods A total of 1790 adults with chronic SCI responded to two self-report assessments, one between 2007 and 2009 (baseline) and another between 2011 and 2014 (follow-up). Average spasticity severity was measured on a numeric rating scale from 0 (no spasticity) to 10 (spasticity as bad as you can imagine). Frequency of prescription medication use for spasticity in the past year was also reported (never, sometimes/weekly, daily). Results About 82.5% of participants had spasticity at baseline and 86.5% at follow-up. There was a significant change in spasticity severity (0.9 ± 2.3;p  < 0.001), corresponding to a 31% increase in mean severity. Overall, the frequency of medication use did not significantly change. At baseline, 55.6% of participants reported using medications for spasticity in the past year; 54.9% reported use at follow-up. Variables significantly associated with spasticity severity included race/ethnicity, age, and spasticity medication use. Conclusions Spasticity is highly prevalent after SCI. Though severity is mild on average, a statistically significant increase was observed over a relatively short natural timeframe. The changes observed in spasticity severity categories (mild, moderate, severe) highlight the need to monitor spasticity in individuals with chronic SCI.